Assessment of Current Energy and Power Generation in the Sunda Strait through Hydrodynamic Modeling with Delft3D and Turbine Evaluation - Suciana, Suciana; Elsa Rizkiya Kencana; Rayhan Al-Ghazali; Sumartini (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
The rapid population growth in Indonesia has significantly driven up energy demand, creating challenges in meeting these needs due to the declining availability of fossil fuels, the main source of power for most energy plants. Given Indonesia’s geographical position as a maritime nation with nearly six million square kilometers of ocean and over eighty-one thousand kilometers of coastline, the country has immense potential for harnessing ocean currents, waves, and tidal energy to develop renewable energy sources. Exploring these unconventional energy resources is crucial for meeting the country’s future energy demands. One of the most promising locations for Ocean Current Power Plants is the Sunda Strait. This research aims to model the ocean currents in the Sunda Strait, using Delft-3D software to assess its potential for Ocean Current Power plant development. The study also includes initial mapping of high-potential areas for energy production. Results from three observation points Sragi, Rimaubalak, and Sangiang indicate that the waters around Sangiang are most suitable for Ocean Current Power Plants with average currents of 0.86 m/s and a maximum of 4.77 m/s in 2023 also 0.938 m/s with maximum 5.20 m/s in 2024. For energy generation, the Gorlov turbine is particularly effective, producing 10642 kW in 2023 and 21285 kW in 2024, albeit with an efficiency of 36.52%. The Darrieus turbine showed a higher efficiency of 45.05%, though it generated slightly less power. Both turbines are deemed highly viable for further development in the Sunda Strait, offering a significant step toward Indonesia's renewable energy goals.